Barbados' national ICT strategic plan : mobile Barbados : building the networked nation - draft report - Babb, Annalee (ACB Knowledge Consultants Mt StandfastBB, 2005)
Assesses the state of ICTs in Barbados; outlines a draft work programme for the development of an ICT plan, includes key projects for implementation.